Immobilized L-arginine on methacrylate polymer as reusable heterogeneous catalyst for crude palm oil transesterification - Erwanto, Erwanto; Warsito, Warsito; Sabarudin, Akhmad; Mardiana, Diah; Iftitah, Elvina Dhiaul (International Journal of Renewable Energy Development, 2026)
The development of enviromentally friendly and reusable heterogenous catalyst has attracted significant attention for sustainable biodiesel production from low-cost feedstocks such as crude palm oil (CPO). This study aims to synthesize and evaluate an L-arginine immobilized methacrylate-based porous polymer as an efficient and reusable heterogenous base catalyst for CPO transesterification. In this study, a porous polymer synthesized from glycidyl methacrylate (GM) and ethylene glycol dimethacrylate (EGD), denoted as poly(GM-co-EGD), was employed as a support matrix for L-arginine immobilization to develop an efficient heterogeneous base catalyst for the transesterification of CPO. The catalyst was prepared via free radical polymerization followed by covalent immobilization of L-arginine onto the porous polymer framework. FESEM analysis revealed a well-developed interconnected porous morphology, which was further supported by textural characterization showing a high BET surface area of 650 m² g⁻¹ and a total pore volume of 2.07 cm³ g⁻¹. FTIR spectra confirmed the successful chemical bonding between L-arginine and the polymer matrix. Thermogravimetric analysis indicated good thermal stability of the polymeric catalyst up to 120 °C, suitable for transesterification conditions. The basic strength evaluated using Hammett indicators showed moderate-to-strong basicity (9.9 < H_ < 12), while quantitative back titration with benzoic acid revealed that the catalyst with a poly(GM-co-EGD):L-arginine ratio of 1:2 exhibited the highest total basicity of 1.01 mmol g⁻¹. Process optimization using Response Surface Methodology with a Box–Behnken design produced a highly accurate quadratic model (R² = 0.9992). Under optimal conditions, a biodiesel yield of 82.34 ± 1.08% was achieved, consistent with model predictions. The catalyst maintained stable performance over five consecutive cycles, demonstrating its potential as a green and sustainable catalyst for biodiesel production from CPO.